IMPORTANCE OF PROFESSIONAL ETHICS FOR LEARNING - Chen, Che-Fei (International Journal of Application on Economics and Business, 2024)
The study focuses on the perceptions of financial students regarding the significance of professional ethics for their education and employment. Data is collected through a questionnaire administered to undergraduate business management students, providing insights into their awareness, importance perception, and self-assessment of professional ethics. The findings indicate that while students recognize the importance of professional ethics, they do not believe it significantly contributes to their academic performance and future careers. Overall, the paper emphasizes the significance of professional ethics for commercial students and suggests strategies to improve ethical competence in education and employment settings.